The Influence Of Employee Seniority And Loyalty On Position Promotion At The Gowa Regency Trade And Industry Service - Intan Intan; Sri Andayaningsih; Zalkha Soraya (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study examines the influence of employee seniority and loyalty on job promotion at the Trade and Industry Service of Gowa Regency. The research is motivated by the importance of fair and transparent promotion systems in public organizations, where both seniority and loyalty are often considered as decisive factors. Employing a quantitative research design, data were collected through structured questionnaires distributed to all 39 employees of the Trade and Industry Service using a saturated sampling technique. The data were analyzed with multiple linear regression supported by SPSS version 30, and the validity and reliability of instruments were tested prior to hypothesis examination. The results demonstrate that seniority has a positive and significant effect on job promotion, as indicated by the t-count value of 3.188, which exceeds the t-table value of 1.686, with a significance level of 0.003. Similarly, employee loyalty shows a positive and significant effect on job promotion with a t-count of 3.151 and the same significance value of 0.003. Furthermore, simultaneous testing confirms that both variables jointly influence job promotion, with an R² value of 0.328, suggesting that 32.8% of the variance in job promotion is explained by seniority and loyalty, while 67.2% is affected by other factors. These findings imply that organizations should design promotion policies that balance seniority, loyalty, and competency to ensure fairness and improve employee motivation.